Improving Employee Performance through Employee Performance Assessment Mechanism at the Malang Regency Transportation Service - R.M Mahrus Ali; Ria; Sinollah (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2025)
This study analyzes the employee performance assessment system at the Malang Regency Transportation Office, based on observations and interviews with several employees. Performance assessments are carried out annually with quarterly evaluations by the head of the sub-division. Evaluations include employee performance, financial administration, and staffing. The assessment process involves several stages: Annual Work Plan (RKT), Performance Agreement, Employee Performance Targets (SKP), and the use of the